The rollout of Community ART Refill Groups in Zimbabwe: a qualitative evaluation. Issue 8 (27th August 2019) - Bochner, Aaron F; Meacham, Elizabeth; Mhungu, Nathan; Manyanga, Phibion; Petracca, Frances; Muserere, Claudios; Gonese, Gloria; Makunike, Batsirai; Wazara, Blessing; Gwanzura, Clorata; Nyika, Ponesai; Levine, Ruth; et al.
Abstract: Introduction: Community ART Refill Groups (CARGs) are an antiretroviral therapy (ART) delivery model where clients voluntarily form into groups, and a group member visits the clinic to collect ART for all group members. In late 2016, Zimbabwe began a nationwide rollout of the CARG model. We conducted a qualitative evaluation to assess the perceived effects of this new national service delivery model. Methods: In March‐June 2018, we visited ten clinics implementing the CARG model across five provinces of Zimbabwe and conducted a focus group discussion with healthcare workers and in‐depth interviews with three ART clients per clinic. Clinics had implemented the CARG model for approximately one year. All discussions were audio recorded, transcribed, and translated into English, and thematic coding was performed by two independent analysts. Results: In focus groups, healthcare workers described that CARGs made ART distribution faster and facilitated client tracking in the community. They explained that their reduced workload allowed them to provide better care to those clients who did visit the clinic, and they felt that the CARG model should be sustained in the future. CARG members reported that by decreasing the frequency of clinic visits, CARGs saved them time and money, reducing previous barriers to collecting ART and improving adherence. CARG members also valued the emotional and informational support that they received from other members of their CARG, further improving adherence. Multiple healthcare workers did express concern that CARG members with diseases that begin with minor symptoms, such as tuberculosis, may not seek treatment at the clinic until the disease has progressed. Conclusions: We found that healthcare workers and clients overwhelmingly perceive CARGs as beneficial. This evaluation demonstrates that the CARG model can be successfully implemented on a national scale. These early results suggest that CARGs may be able to simultaneously improve clinical outcomes and reduce the workload of healthcare workers distributing ART.